2016
DOI: 10.1016/j.psychres.2016.04.120
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines and nuclear factor-kappa B activation in adolescents with bipolar and major depressive disorders

Abstract: Adults with bipolar disorder (BD) and major depressive disorder (MDD) have higher circulating levels of proinflammatory cytokines than healthy controls. However, it is not known whether pediatric-onset patients with BD or MDD show increases in levels of inflammation or activation of nuclear factor kappa B (NF-κB), a key transcription factor in inflammatory signaling. Circulating levels of inflammatory cytokines, as well as spontaneous and stimulated levels of activated NF-κB in total peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 51 publications
(66 reference statements)
1
58
1
1
Order By: Relevance
“…The first study (18 BD patients, 13 major depressive disorder [MDD] patients and 20 HCs) found significantly higher levels of nuclear factor kappa beta (NF-κβ) in peripheral blood mononuclear cells, monocytes, and lymphocytes, higher IL-1β plasma levels, and greater TNF-α-induced elevations in NF-κβ in adolescents with mood disorders than in HCs. 241 The second study (40 BD patients and 20 HCs) found elevated IL-6 and TNF-α levels among adolescents with PBD. 242 …”
Section: | Peripheral Biomarkersmentioning
confidence: 94%
“…The first study (18 BD patients, 13 major depressive disorder [MDD] patients and 20 HCs) found significantly higher levels of nuclear factor kappa beta (NF-κβ) in peripheral blood mononuclear cells, monocytes, and lymphocytes, higher IL-1β plasma levels, and greater TNF-α-induced elevations in NF-κβ in adolescents with mood disorders than in HCs. 241 The second study (40 BD patients and 20 HCs) found elevated IL-6 and TNF-α levels among adolescents with PBD. 242 …”
Section: | Peripheral Biomarkersmentioning
confidence: 94%
“…When considering the potential role of TNFR2 in mood disorders, it is also notable that several pathways activated during transmembrane TNFR2 forward signaling have been implicated in mood disorder pathology, including mitogen‐activated protein kinase, PI3K/Akt and NF‐κB signaling . For instance, mitogen‐activated protein kinase blockade induces depressive symptoms in rats and inhibits the antidepressant effects of ketamine .…”
Section: Tnfr2: Structure Function and Possible Role In The Pathophymentioning
confidence: 99%
“…For instance, mitogen‐activated protein kinase blockade induces depressive symptoms in rats and inhibits the antidepressant effects of ketamine . Elevated NF‐κB activity has been implicated in bipolar disorder, with adolescent bipolar disorder patients showing increased NF‐κB activation in peripheral blood and immune cells, compared with healthy control individuals . Furthermore, recombinant human TNF administration induces greater increases in NF‐κB levels in adolescent mood disorder patients, compared with controls, with NF‐κB elevations associated with exacerbation of depressive symptoms .…”
Section: Tnfr2: Structure Function and Possible Role In The Pathophymentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of BD is yet to be well understood, while recent studies have indicated that abnormal immunological functions may be a contributing factor [38][39][40][41][42]. Recently, positron emission tomography (PET) studies have shown microglial overactivation in the brain of patients with various psychiatric disorders [43][44][45]; [9] including bipolar disorder [42].…”
Section: Mechanisms Of Neuroinflammationmentioning
confidence: 99%